PENERAPAN METODE STOPWATCH TIME STUDY UNTUK MENENTUKAN WAKTU BAKU PADA PROSES PERAKITAN TAMIYA: (Studi kasus di Laboratorium Ergonomi Universitas Serang Raya) - Yuslistyari, Eka Indah; Marseliana, Dea; Age Fidianto, Ade (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2025)
Tamiya assembly standard time measurement research was conducted at the Ergonomics Laboratory of Serang Raya University. The main objective of this study is to determine the standard time required in each work element, and identify inefficient activities so that the assembly process can be optimized. Data collection is done through direct observation by measuring the time of each work element of the Tamiya car assembly directly. The research method uses the Stopwatch Time Study method to analyze work time in the Tamiya car assembly process based on a 95% confidence level and a 5% accuracy level. In assembling Tamiya, there are 5 work elements with standard time in the work element of installing wheels and gears, (44.96 seconds), installing tires and connecting gears, (22.83 seconds), installing switches, (22.8 seconds), installing dinamos, (27.75 seconds), installing batteries and bodies, (23.31 seconds). So that the measurement of the standard time for assembling Tamiya at the Ergonomics Laboratory of the University of Serang Raya in the Work Design Analysis practicum is 151.13 seconds. The results of the study are expected to be a reference in the implementation of Work Design Analysis practicum activities.